IMPACTO DE LAS CONDICIONES DE LOS SITIOS DE TRABAJO Y SU RELACIÓN CON LAS POSTURAS FORZADAS EN EL PERSONAL DE OBRAS PÚBLICAS PARA UN GAD MUNICIPAL - LEÓN ENRÍQUEZ, YISBELL MIKAELA (2025)
This study analyzes the impact of workplace conditions on the adoption of awkward postures among Public Works personnel of the San Jacinto de Buena Fe Municipal Government (GAD).